FIVE WAYS TO BUILD INTERCULTURAL COMPETENCE AND CONFIDENCE IN YOUR CLASSROOM - Normatova, Aziza (Educational Research in Universal Sciences, 2024)
Intercultural competence is the ability to interact and communicate with people from different cultures in a respectful and effective way. It is the bridge between diversity and inclusion and is key to creating welcoming learning environments. True intercultural competence cannot exist without recognizing diverse identities and making intentional steps to be inclusive to people of varying backgrounds.